(723) On Economic Balances and Alternative Methods of Valuation حول الموازين الاقتصادية وطرق التقييم البديلة - M. El-Imam, M. (INP, 2023)

(untitled)
This study explores the importance of consistency in economic balances, emphasizing that the values of resources and uses should match corresponding physical flows. It highlights the need for stable flow values when recalculated with different prices, so variations only reflect price changes. Economic balances are not just accounting tools but must align with the structural realities of an economy. The choice of valuation principles should depend on the intended economic analysis. In national budgeting, the focus shifts to national income rather than production, dividing output into current and capital uses, as well as domestic and foreign components, in line with economic theory.